Trends in depression diagnosis and consumption of antidepressants in Lithuania in 2004–2009 - KAVALIAUSKIENĖ, Liubov; PEČIŪRA, Rimantas; ADOMAITIENĖ, Virginija (Acta medica Lituanica, 2011)
Background. One in five people affected by depression will not recover fully from a first episode, and in 70–80% of those achieving remission, depression will recur. The aim of this study was to evaluate the consumption of antidepressants during six years (2004–2009) in Lithuania, to analyze the trends in the diagnosis of depression and its compliance with the use of antidepressants for the future investigation of rationalizing medicamentous depression treatment costs in Lithuania opportunities. Materials and methods. Data on the total sales of antidepressants were obtained from the IMS (Intercontinental Marketing Service) Health Incorporated. The data were calculated by the DDD (Defined Daily Dose) methodology and expressed in DDDs per 1.000 inhabitants per day. Data on depression diagnosis were obtained from the National Psychiatric Health Centre and expressed as the number of diagnoses in total and by depression types and gender. Results. The total consumption of antidepressants increased from 10.17 DDD / 1000 inhabitants / day in 2004 to 15.0 DDD / 1000 inhabitants / day in 2009. The number of total depression diagnoses increased by 12%. The number of first time diagnosed depression increased not as significantly as relapsed depression diagnoses – by 27%. In 2009, women were diagnosed with depression 4.5 times more frequently than men. Moreover, depression relapse numbers grew up by 33% during the six study years among women. Conclusions. During the study period, the consumption of antidepressants increased by 48%. Women were diagnosed with depression more frequently than men. The results of our study show that the number of depression diagnoses are growing because of depression relapse in women. Keywords: antidepressants consumption, depression relapse, pharmacoeconomics